Standardization of Web Content Accessibility - E. A. Kosova (Открытое образование (Москва), 2020)
Purpose of research. The paper provides an overview of international and state standards in the field of web resources accessibility for persons with disabilities in order to create guidance for using existing standards in the development of industry regulations, including the area of e-learning technologies.Results of recent studies indicate low accessibility of Russian-language mass open online courses for people with disabilities. Studying the content and implementing mechanisms of existing web accessibility standards can be useful for finding effective solutions that will help to provide an access to educational online services for students with special needs.Material and methods. The list of accessibility policies available on the official website of the Web Accessibility Initiative (WAI) was used as a basis for the review. Original versions of international and state standards pertaining to the web-accessibility policies have been studied. The study found relevant updates and additional documents, which were also included into the review. The materials of the Rosstandart (Federal Agency on Technical Regulating and Metrology) and Tekhekspert resources were used for the analysis of the Russian Federation standards.Results. The provisions of the international standard in the field of web accessibility – the Web Content Accessibility Guidelines (WCAG) – have been studied. It was found that almost all the foreign national standards are identical to one of the latest versions of the WCAG or are an adapted version of WCAG. It justified the need to follow the WCAG guidelines for developing new policies and accessibility standards. A comparative analysis of the national state standard GOST R 52872-2019 and WCAG 2.1 revealed the identity of the requirements. At the same time, GOST R 52872-2019 extends its requirements on any information presented in the electronic digital form that is utilizing web technologies or similar technologies. The web accessibility requirements governing the accessibility of educational resources for individuals with disabilities were not found in the existing Russian Federation standards in the field of e-learning.Conclusion. It is necessary to rely on the current international accessibility standard WCAG 2.1 in the development of industry standards in the field of information and communication technologies. The national state standard GOST R 52872-2019 can be recommended as a basis for modification industry standards of the Russian Federation, in particular, in the field of e-learning in terms of web accessibility.